A STUDY OF TYPE AND INTENSITY OF DISEASE INFECTING BANANA PLANTS Musa sp AT TEGALAGUNG VILLAGE SEMANDING SUBDISTRICT - Supiana Dian Nurtjahyani; Devi Shyntya Agustin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Diseases affecting banana plants are very detrimental to farmers as these can lower production and economic income. The purpose of this study was to determine the type and intensity of the disease affecting banana plants. This research was an observational analytic study that observe and analyze condition or symptoms of diseases affecting banana plants in Tegalagung village, Semanding subdistrict, Tuban as many as 38 samples. Parameters observed were type of disease and measure intensity of the disease, data obtained were analyzed descriptively. Based on the symptoms that occurred on the leaves, the study found four disease types affecting banana plant that were fusarium wilt, bacterial wilt (Blood), Sigatoka leaf spot and stunting disease. The diseases intensity were 50% of Fusarium wilt; 26,66% of bacterial wilt (Blood); 26.32% of Sigatoka leaf spot and 15.38% of stunting disease. Conclusion of the study, the highest intensity of the disease that attacks banana plants is Fusarium wilt as high as 50%.